"You Can't Put Everything I've been through into Professional Development": Transformative Literacy Coaching in an "Underperforming" High School. Issue 1 (2nd January 2021) - Lesley, Mellinee; Beach, Whitney; Smit, Julie
ABSTRACT: Because the role of literacy coach as a transformative change agent is a goal of many literacy programs, we set out to examine the process by which a literacy coach becomes a leader and transforms the learning environment of an "underperforming" high school being monitored by the state education department for low test scores. In the present study we followed Ms. Hill (all names are pseudonyms), a literacy coach recruited to transform the English curriculum at Trenton High School over a two-year period-of-time to learn more about the literacy crisis many high schools are facing,  the necessity for "transformative" coaching, and specific conditions that foster the development of transformative literacy coaches. We discuss key phenomena that helped the literacy coach design a transformative role.